2009
DOI: 10.2166/wst.2009.345
|View full text |Cite
|
Sign up to set email alerts
|

Use of near infrared spectroscopy in monitoring of volatile fatty acids in anaerobic digestion

Abstract: Recently biogas production from agricultural sources has rapidly developed. Therefore the demands on biogas plants to optimise the efficiency of the anaerobic digestion (AD) process have grown immensely. At present there is no online-supervision tool available to monitor the AD process, but costly and time-consuming chemical analyses are necessary. The possibility to use near-infrared spectroscopy (NIRS) in order to track relevant process parameters like total volatile fatty acids (VFA), acetic acid and propio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 12 publications
(14 reference statements)
1
18
0
1
Order By: Relevance
“…Precipitation of insoluble inorganic P during anaerobic digestion tends to reduce the concentration of immediately available P and micronutrients [77], although this does not usually result in P deficiency in crops [93,94], perhaps because the N:P ratio in the untreated manure is higher than the N:P requirement of most plants [76]. Volatile fatty acids and other labile organic compounds are formed as intermediates in the anaerobic digestion process [95,96]. If these compounds are still present when bioslurry is applied to the soil, they provide a readily available source of C, which could result in the available nutrients being immobilized or lost from the soil [97].…”
Section: Bioslurry Produced By Anaerobic Digestion 51 Composition Omentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitation of insoluble inorganic P during anaerobic digestion tends to reduce the concentration of immediately available P and micronutrients [77], although this does not usually result in P deficiency in crops [93,94], perhaps because the N:P ratio in the untreated manure is higher than the N:P requirement of most plants [76]. Volatile fatty acids and other labile organic compounds are formed as intermediates in the anaerobic digestion process [95,96]. If these compounds are still present when bioslurry is applied to the soil, they provide a readily available source of C, which could result in the available nutrients being immobilized or lost from the soil [97].…”
Section: Bioslurry Produced By Anaerobic Digestion 51 Composition Omentioning
confidence: 99%
“…Treatment of organic wastes before application by anaerobic digestion or composting, allows losses of nutrients to be reduced, and allows C-rich organic wastes to be included in crop nutrition that could not otherwise be used. Bioslurries from anaerobic digestion also provide a high input of immediately available nutrients that promotes a rapid response from the crop [91], but because C rich materials have been decomposed before they are added to the soil, the risks of immobilization are reduced compared to untreated wastes [95,96]. Phytotoxicity is also reduced by the digestion process, so the bioslurry can usually be applied directly to the crop when nutrients are needed, greatly reducing the risks of nutrient loss by leaching or volatilization.…”
Section: The Potential Of Biogas Digesters To Improve Soil Fertility mentioning
confidence: 99%
“…Jacobi et al [53] reported the use of near infrared spectroscopy for monitoring of a full-scale agricultural AD plant processing maize silage. It was stated that according to German authorities, 4000 agricultural AD plants were in operation in Germany by the end of year 2008.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…Several studies have pointed out that the determination of individual volatile fatty acids will also contribute towards improved understanding of anaerobic digestion and prevent a failure of the process [21,25]. Therefore, concentration and composition of the VFA are the best parameters to reflect the metabolic state of the biochemical process in anaerobic digester and this information would enable the optimal feeding of the biohydrogen or biogas plant [26]. Furthermore, the determination of impurities from crude glycerol such as methanol in the anaerobic digester is relevant as well as the monitoring of VFA due to its inhibitory character in high levels of concentration in biohydrogen production [7,27,28].…”
Section: Introductionmentioning
confidence: 99%